A Factor Analysis of the Impact of Digitalisation on the Banking Industry - Druhova, Vira; Hirna, Oleksandra; Fostyak, Vira (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: This paper examines the impact of digitalisation on the banking industry. Research done to date in the field has led to conclusions mainly in favour of digitalisation. Foremost among the positive arguments is that the quality of banking is improved, with customer service sped up; internal business processes are optimised; and the profitability and efficiency of banking are both boosted. We questioned these arguments and used factor analysis to examine the relationship between profitability, the share of problem bank loans and online payments in 87 countries.Research Design & Methods: Factor analysis, used to determine the correlation between different variables; retrospective analysis, which made it possible to analyse the data taking into account the factor of time; a systematic approach to identifying problem areas and drawing conclusions from the study.Findings: The results of the study showed digitalisation to have a negative impact on the indicators of banking activity analysed. Countries with a higher level of Internet use for payments have lower returns on banking assets and have a higher share of problem assets in their portfolios. Analysing data from 2014, we found the year to be somewhat of a turning point for banking. Banks were not as fully engaged with digital technologies and innovations. As a result, fintech companies quickly competed with banks and gained market share. Data from 2017 show a decrease in the impact of the share of payments made via the Internet on the return on bank assets. However, a comparison of 2014 and 2017 showed, on the contrary, a worsening of the impact of the relationships between the share of online payments and the quality of banks’ loan portfolios. Thus, in countries with a higher level of Internet use for payments, the riskiness of the banking business increases.Implications / Recommendations: It is therefore appropriate for banks to use digital technologies not only to increase sales and improve the quality of customer service but also to improve scoring and financial monitoring systems. Innovative AI and big data systems and customer identification allow for a better assessment of the borrower’s creditworthiness and potential risks. Attention should likewise be paid to improving the population’s financial literacy. Banks must also take responsibility for educating their customers through digital technology. Chatbots, which are now used primarily to increase sales and advise customers, can serve as a training format and draw attention to customers’ typical financial mistakes. In addition, chatbots can provide advice to customers on the profitable investment of free funds.Contribution: Digitalisation provides banks with considerable opportunities, while at the same time creating risks banks have not yet learned to deal with.